(untitled) - Finkelstein, Eric A. (Hoboken, N.J., 2008)
The authors highlight fascinating new scientific research into the causes of obesity and offer tips on lightening your load over the long haul. This book serves up a healthy selection for public and academic library business collections.
Keywords: Obesity,Béo phì; Economic aspects,Khía cạnh kinh tế; United States,Hoa Kỳ